Mechanically rigid supramolecular assemblies formed from an Fmoc-guanine conjugated peptide nucleic acid - Vasantha Basavalingappa (Nature Portfolio, 2019)
DNA is an attractive nanomaterial, yet limited compared to polyamides due to low stability and mechanical issues. Here, the authors combine polyamide and DNA characteristics to form mechanically rigid self-assembled peptide nucleic acid based materials with high stiffness and Young’s modulus.